2004
DOI: 10.1590/s1517-86922004000200006
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos agudos da atividade contra-resistência sobre o gasto energético: revisitando o impacto das principais variáveis

Abstract: INTRODUCTIONComprehension of the factors that affect energy balance is of key importance in understanding the regulation of body mass. Energy balance is determined, on the one hand, by energy consumption and, on the other, by energy expenditure. When these factors are not in equilibrium, it may result in an excessive accumulation or reduction of the energy stored endogenously as body fat. However, obesity is the most frequent result of the unbalance between food ingestion and energy expenditure.The number of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
18

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
0
12
0
18
Order By: Relevance
“…17 Each of these resistance protocols have different metabolic and hormonal responses regarding the difference in the intensity of exercise and rest time between sets, one of the factors in determining energy expenditure during resistance exercise. 18,19 Kraemer et al examined the levels of certain hormones including growth hormone, and cortisol as well as lactate level in response to resistance exercise with 6 different protocols. 20 Studies show that intensity and duration of exercise can affect gene expression and plasma levels of these hormones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Each of these resistance protocols have different metabolic and hormonal responses regarding the difference in the intensity of exercise and rest time between sets, one of the factors in determining energy expenditure during resistance exercise. 18,19 Kraemer et al examined the levels of certain hormones including growth hormone, and cortisol as well as lactate level in response to resistance exercise with 6 different protocols. 20 Studies show that intensity and duration of exercise can affect gene expression and plasma levels of these hormones.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Hormonal and metabolic responses to resistance exercise are complex processes and an integrated system for signalling to a large group of target cells. 18 As one of the factors, 23 visfatin and insulin are affected in response to exercise. Considering the role of resistance training in improving insulin sensitivity, 24 comparison of visfatin and its possible impact on the response to resistance exercise protocols can show important potential mechanisms on the role of visfatin in insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Ponderal reduction is also related with chronic alterations of physical activities, that is, of the resting metabolic rate (RMR). The RMR is defined as the energetic cost necessary to the physiological processes maintenance in the post-absorptive state, reaching up to 60-70% of the total energetic cost, depending on the physical activity level (21) . The high interest on ponderal reduction is due to the fact that obesity is currently considered by the World Health Organization a public health problem (22) .…”
Section: Introductionmentioning
confidence: 99%
“…An estimate considering the current prevalence of obese individuals highlights that if such proportion remains, in the year 2230 100% of the North-American population will be obese (23) . Analyzing the Brazilian reality, Meirelles and Gomes (21) showed that in Rio de Janeiro 44% of the men and 33% of the women in the age group from 26 to 45 years present overweight or obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation